Grotesco e ironia em Macário de Álvares de Azevedo: transgressão, spleen e utopia - Anfora, Adriana Ingrid (2012)
This analysis aims to study drama Macário of Álvares de Azevedo, in order to point out each of the concepts of the grotesque, irony and trangression, utopia and spleen, and see how each element composing the text structure azevediana, taking into view of the relationship of antagonistic terms that permeates the opposing aspects of reality and dream, enabling thus a macabre atmosphere, the irruption of the supernatural in terms of imbalances of the man who lives below the dilemma in moral precepts established by society in which he lives or let nature guide their principles and values. The grotesque being investigated in this dissertation in the romantic who seeks, above all, the revolto of the individual against the reality that we can live fully and for that reason, it creates a parallel world that their aspirations to take part in this process